Component-based software development : case studies - Lau, K.-K. (Kung-Kiu), 1953- (New Jersey : World Scientific, 2004)
Component-based software development (CBD) is an emerging discipline that promises to take software engineering into a new era. Building on the achievements of object-oriented software construction, CBD aims to deliver software engineering from a cottage industry into an industrial age for Information Technology, wherein software can be assembled from components, in the manner that hardware systems are currently constructed from kits of parts. This volume provides a survey of the current state of CBD, as reflected by activities that have been taking place recently under the banner of CBD, with a view to giving pointers to future trends. The contributions report case studies - self-contained, fixed-term investigations with a finite set of clearly defined objectives and measurable outcomes - on a sample of the myriad aspects of CBD. The book includes chapters dealing with COTS (commercial off-the-shelf) components; methodologies for CBD; compositionality, i.e. how to calculate or predict properties of a composite from those of its constituents; component software testing; and grid computing.
A Survey of Proposals for Architecting Component Software / T. Ihm (VTT Electronics, Finland) -- Describing Specifications and Architectural Requirements of COTS Components / L. Iribarne (University of Almeria, Spain), J.M. Troya, A. Vallecillo (University of Magala, Spain) -- Definition of COS Software Component Acquisition Process -- The Case of a Telecommunication Company / P. Ulkuniemi, V. Seppanen (University of Oulu, Finland) -- The Library Systems Product Line: A Case Study Demonstrating the KobrA Method / J. Bayer, D. Muthig (Fraunhofer Institute for Experimental Software Engineering, Germany) -- Component-based Sy, stetn Design and Composition: An ALpxtoriented Approach / P.J. Clemente, J. Hernindez, J.M. Murillo, M.A. Pkrez, F. Sinchez (University of Extremadura, Spain) -- Properties of Software Systems Synthesized from Components / D. Hamlet (Portland State University, USA), D. Mason, D. Woit (Ryerson Polytechnic University, Canada) -- Component-based Measurement and Control Software fur Embedded Systems / W. Maydl, H. Sick, W. Grass (University of Passau, Germany) -- Fault-based Testing of CORBA Component Sofnyare / S. Ghosh (Colorado State University, USA), A.P. Mathur (Purdue University, USA) -- ARIFS Methodology: A Case Study / R.P. Diaz Redondo, J.J. Pazos h a s, A. Fernandex Was (University of Vigo, Spain) -- REBOUND: A Framework for Automated Component Adaptation / J. Penix (NASA Ames, USA), P. Alexander (University of Kansas, USA) -- A Web-enabled Component-based Architecture for Legacy Applications / G. Wang, R. Robinson, S. Sripada (The Boeing Company, USA) -- Component-based Problem Solving Environments for Compurutional Science / M. Li (Brunel University, UK), 0.E Rana, D.W. Walkcr, M. Shields, Y. Huang (Cardiff University, UK).
Includes bibliographical references (pages 297-299) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Component software -- Development; Software engineering; Composants logiciels -- Développement.; Génie logiciel; REFERENCE -- General; Software engineering; Component software -- Development; Software engineering